Albinismo platinado en Liomys pictus (Mammalia: Heteromyidae) - Martínez-Coronel, Matías; Bautista, Rogelio; Verona-Trejo, Martha Isela (THERYA, 2013)
Albinism is a genetic abnormality, it can manifest as hypopigmentation or absence of color in skin, fur and eyes. The survival rate of wild animals with albinism is usually low. This paper reports the record of a platinum albino female of painted spiny pocket mouse Liomys pictus from Guerrero state, Mexico. Keywords: Albinism, oak forest, pigmentation, Rodentia, small mammals